2018
DOI: 10.1302/0301-620x.100b7.bjj-2017-1449.r1
|View full text |Cite
|
Sign up to set email alerts
|

Robotic-arm assisted total knee arthroplasty is associated with improved early functional recovery and reduced time to hospital discharge compared with conventional jig-based total knee arthroplasty

Abstract: AimsThe objective of this study was to compare early postoperative functional outcomes and time to hospital discharge between conventional jig-based total knee arthroplasty (TKA) and robotic-arm assisted TKA. Patients and MethodsThis prospective cohort study included 40 consecutive patients undergoing conventional jig-based TKA followed by 40 consecutive patients receiving robotic-arm assisted TKA. All surgical procedures were performed by a single surgeon using the medial parapatellar approach with identical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
238
3
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(270 citation statements)
references
References 28 publications
10
238
3
5
Order By: Relevance
“…While custom cutting guides offer theoretical advantages, the majority of mid-to-long-term studies assessing their efficacy have demonstrated nonsuperiority [20][21][22][23][24][25][26] . Although the true value and cost-effectiveness of robotic technology have been debated, the use of robotic-arm assistance has demonstrated superiority to patient-specific instrumentation 27 and has shown the ability to improve TKA alignment in multiple studies 19,[28][29][30][31][32] . The findings of the current study, especially if alignment outlier status is linked to increases in implant failure in follow-up studies, may justify the increased use of these technologies in the future.…”
Section: Multivariate Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…While custom cutting guides offer theoretical advantages, the majority of mid-to-long-term studies assessing their efficacy have demonstrated nonsuperiority [20][21][22][23][24][25][26] . Although the true value and cost-effectiveness of robotic technology have been debated, the use of robotic-arm assistance has demonstrated superiority to patient-specific instrumentation 27 and has shown the ability to improve TKA alignment in multiple studies 19,[28][29][30][31][32] . The findings of the current study, especially if alignment outlier status is linked to increases in implant failure in follow-up studies, may justify the increased use of these technologies in the future.…”
Section: Multivariate Analysismentioning
confidence: 99%
“…As a result of the link between implant alignment outliers and early implant failure, efforts have been made to optimize alignment with the use of robotic navigation and patient-specific instrumentation [19][20][21][22][23][24][25][26][27][28][29][30][31][32] . However, little work has been conducted to identify the primary surgeon-specific factors that drive these outliers in order to understand the optimal patient populations in which to utilize this expensive technology.…”
mentioning
confidence: 99%
“…As valgus knees can require a greater amount of planning and precision, RA technology may be an option for surgeons to plan the case and make intraoperative component adjustments prior to bone cuts [5]. In literature, RA technology has been shown to reduce in post-operative pain and opioid usage which provides benefits to the patient and the hospital system [6]. This study required no intentional soft tissue releases, indicating RA TKA may reduce post-operative pain.…”
Section: Discussionmentioning
confidence: 84%
“…These lower rTKA patient costs are likely attributable to the significantly lower index costs, increased likelihood of being discharged to home, shorter LOS, and decreased readmission rates, when compared to mTKA patient costs. Additional contributing factors may include a number of RAA-associated clinical, radiographic, and patient outcome advantages [4][5][6][7][8][9][10] . Future studies should build on these findings, by performing hospital and surgeon-specific cost analyses.…”
Section: Discussionmentioning
confidence: 99%